PENINGKATAN PRODUKTIVITAS TERNAK ITIK MELALUI SISTEM PEMELIHARAAN INTENSIF DAN PENGGUNAAN PAKAN LOKAL - ,, Zurmiati; ,, Arief; Ciptaan, G.; ., Mirnawati (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana Mengabdi, 2024)
The duck farming business is quite popular among the people of Kubung District, Solok Regency. The sustainable availability of rice bran in this area also supports the development of duck farming. However, the duck population is currently decreasing due to the need for more public knowledge about duck-rearing systems and the high feed cost. This service aims to increase breeders' insight, mindset, and motivation in raising ducks. The ultimate goal of this service is to improve the welfare of the community, especially those who are members of farmer groups, such as livestock groups, by applying science and technology, namely using local materials as ingredients for duck rations. The method to support the implementation of this service is a combination of counseling, training, guidance, and monitoring. The results of outreach and training activities delivered by resource persons to duck breeders provide knowledge to all participants. This knowledge is beneficial for breeders in preparing duck rations according to the rearing period, and breeders can use potential local feed ingredients in the area, such as rice bran. Based on the service carried out, it was concluded that breeders in Kubung District, Solok Regency, have the potential to develop duck farming. This can be seen from the availability of land for cages, the availability of local feed ingredients, especially rice bran, and finally from the enthusiasm of the community in developing their livestock business.